QALBUN HEALING BERBASIS TASAWUF : UPAYA MENYEHATKAN JIWA TERHADAP HOMOSEKSUAL - Azam Syukur Rahmatullah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
The healing to the homosexual is not easy, it is not just to do ritualistic daily-worship and after that to be healed, certainly it is not easy. The handling for them is special, the central zone is in the heart. It the mean, the central heating for the homosexual is in the heart, called qalbun healing. The approach of it using qalbun healingis special, caused rich of spiritualistic-religious, it named tasawuf with the thariqah to guide the person go to an-nur Allah. There are many religious-method was used in the homosexual that wants to heal and having good behavior by mursyid that teacher-spiritual avowed virtuous, knowledge, and behavior. The formula, these are;taubat an-nasuha, al-zuhud, al-wara’, al-tawakal, al-mahabbah dan al-ma’rifah. The formula can estrange from homosexual behavior if welldoing and istiqamah.